Enhancing the Marginalized Youth Media Participation Through Formation of a Nation Building Action Plan with Intervention Study Design - Mohd Sani, Mohd Azizuddin; Abdul Rahman, Zainatul Shuhaida; Ehret, Marian; Ahmad, Mohd. Khairie; Aboo Talib, Kartini; Ahmad, Noor Sulastry Yurni (Asia Pacific Media Educator, 2021)
Malaysian marginalized youth participation in nation building through various media platforms is low. Therefore, an action plan was developed to enhance the social, political and economic participation of youth in marginalized communities through media utilization. The action plan consists of target items and approaches to conduct activities. Eight media-participation-related modules were also tested in an intervention study. The modules were targeted at increasing the level of youth media, social and political participation. Various agencies such as the Malaysian Youth Council, were involved to help realize the plan aims. Results from the stakeholders’ reviews indicated that more efforts have to be carried out to expose these youth to good practices in the use of social media for participation purposes. The findings also concluded that this action plan is well-formed, can serve as a guide, allows integration of cultural harmony and offers empowerment to the youth.